2016
DOI: 10.1111/head.12793
|View full text |Cite
|
Sign up to set email alerts
|

Association of Migraine Headaches With Suicidal Ideation Among Pregnant Women in Lima, Peru

Abstract: Background Suicide is a leading cause of maternal death globally, and suicide prevalence rates have been shown to be increased in those with migraine. No previous study has examined the association between migraine and suicidal ideation during pregnancy. Objective To examine the association between migraine and suicidal ideation among a cohort of pregnant women. Methods A cross-sectional study was conducted among 3,372 pregnant women attending prenatal care clinics in Lima, Peru. Suicidal ideation and depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 55 publications
4
32
0
Order By: Relevance
“…The phenomenon of suicidal ideation and association with migraine headache was also explored in this review. A seminal study by Friedman et al (2016) found participants with migraines were at greater risk of experiencing suicidal ideation compared to those diagnosed with probable migraines. Authors acknowledged further research into this subject is warranted, however it should be an important consideration for midwives when caring for women who suffer from migraines during pregnancy or have a history of migraines.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…The phenomenon of suicidal ideation and association with migraine headache was also explored in this review. A seminal study by Friedman et al (2016) found participants with migraines were at greater risk of experiencing suicidal ideation compared to those diagnosed with probable migraines. Authors acknowledged further research into this subject is warranted, however it should be an important consideration for midwives when caring for women who suffer from migraines during pregnancy or have a history of migraines.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Its manifestations range from inability to lead a productive life due to loss of work/school days to withdrawal from social and leisure activities which ultimately affect the quality of life [ 9 , 10 ]. Additionally, migraine disorders have been associated with psychiatric comorbidities including substance abuse, mood and anxiety disorders, depression, and suicidal behaviors [ 11 20 ]. Suicidal thoughts and behaviors (hereafter referred to as suicidal behaviors) which include suicidal ideation, plans, and attempts are predictors of completed suicide [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Annually more than half a million people die due to suicide; while three-fourth of this deaths are in low and middle income countries (LAMICs) [ 23 ].Despite the profound personal, societal, and economic consequences both these problems have; knowledge pertaining to their association remain limited, particularly in LAMICs. Though previous research have shown the association between migraine and suicidal behaviors [ 16 , 19 , 20 , 24 ]; no studies in sub-Saharan Africa have investigated this association. Due to the high burden of migraine in sub-Saharan Africa and the existing knowledge gap, we sought to evaluate the extent to which migraine headaches are associated with suicidal behaviors, including suicidal ideation, plan, and attempts, in a well-characterized study of urban dwelling Ethiopian adults.…”
Section: Introductionmentioning
confidence: 99%
“…pregnant women 14 , adolescents 1517 and young adults 4, 18 . Previous cohorts have included clinic 14 and community based 4, 15, 16, 18 samples. To our knowledge, the only previous nationally-representative population based study was done in a population of adolescents 17 .…”
Section: Introductionmentioning
confidence: 99%
“…While two studies have examined suicide in migraineurs, 12,13 few studies have examined suicidal behaviors (eg, suicidal ideation, suicide attempts). All of these studies have been relatively small or examined the association in targeted populations, ie, pregnant women, 14 adolescents, [15][16][17] and young adults. 4,18 Previous cohorts have included clinic 14 and community based 4,15,16,18 samples.…”
Section: Introductionmentioning
confidence: 99%